Effectiveness of single-volume continuous jogging and intermittent running on short-term blood glucose in elderly patients with type 2 diabetes mellitus - Lv, Yan; Wu, Yue-Mei; Wang, Li-Li; Yan, Li-Li; Ge, Lin; Du, Xun; Liu, Jing-Juan (Frontiers in Medicine, 2026)
ObjectiveTo investigate the effects of different single-volume exercise modalities on physiological indicators, including blood glucose, heart rate (HR), and fatigue, in elderly patients with type 2 diabetes mellitus (T2DM). Additionally, this study assessed participants’ subjective perceptions and acceptance of these exercises to inform the development of reasonable and effective exercise prescriptions.MethodsThirty elderly patients with T2DM participated in this self-controlled, pre-post intervention study. Experiments were conducted over three separate days: two exercise days involving continuous jogging (CJ) and intermittent running (IR), with the sequence randomized, and one control day without exercise. Participants in the CJ group were instructed to run at a self-perceived moderate intensity. Based on pre-test results, running speed was set between 4–6 km/h for approximately 20–30 min. In the IR group, participants ran at a preset speed of 6–8 km/h for 4 min, followed by 3 min of stationary rest, repeating this cycle throughout the session. Blood glucose was measured at fasting, pre-exercise, immediately post-exercise, at 11:00 a.m. (before lunch), and at 4:00 p.m. Blood glucose data were analyzed using two-way repeated measures ANOVA, followed by one-way ANOVA with post hoc tests to identify specific differences. HR and rating of perceived exertion (RPE) were analyzed using one-way ANOVA, while blood pressure and PACES scores were compared using paired t-tests.ResultsParticipants had a mean age of 68.20 ± 8.13 years, diabetes duration of 8.42 ± 5.07 years, and body mass index (BMI) of 24.46 ± 3.54 kg/m2. Blood glucose levels decreased immediately after exercise in both modalities and were significantly lower than pre-exercise values. At 11:00 a.m., blood glucose was significantly lower in the exercise groups compared to the control group, whereas at 4:00 p.m., no significant differences were observed among the groups. No differences in blood glucose levels between CJ and IR were identified at any time point. Immediately post-exercise, HR reached 73% of the maximum in the CJ group and 84% in the IR group. There were no significant differences in RPE scores between the exercise modalities.ConclusionCJ and IR had similar effects on short-term blood glucose regulation. However, participants demonstrated greater acceptance of IR, suggesting it may be more suitable for elderly patients with T2DM.